(untitled) (Research, Society and Development, 2022)
This study presents the analysis and characterization of the corrosive process in the metallic material that makes up the hull of a shipwreck in 1905 in the Baia de Todos os Santos in the city of Salvador - Bahia - Brazil. Samples were collected from fragments of the shipwreck’s hull by scuba diving. The results obtained through techniques such as electrochemistry and scanning electron microscopy, allowed the analysis of the process and products of corrosion in the metallurgical structure, as well as metallography to verify the phases present in its structure after the manufacturing process in the last century. The constitution of the Black Adder’s hull, built in 1869, consists of a low carbon steel alloy, containing high levels of impurities, mainly phosphorus and sulfur, demonstrating the low metallurgical quality of the time.